2013
DOI: 10.4269/ajtmh.13-0308
|View full text |Cite
|
Sign up to set email alerts
|

Access to Safe Water in Rural Artibonite, Haiti 16 Months after the Onset of the Cholera Epidemic

Abstract: Haiti has the lowest improved water and sanitation coverage in the Western Hemisphere and is suffering from the largest cholera epidemic on record. In May of 2012, an assessment was conducted in rural areas of the Artibonite Department to describe the type and quality of water sources and determine knowledge, access, and use of household water treatment products to inform future programs. It was conducted after emergency response was scaled back but before longer-term water, sanitation, and hygiene activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 12 publications
3
28
0
Order By: Relevance
“…These results are consistent with the findings of other studies that demonstrated improved sources are not necessarily safe. 5,6,8,[25][26][27][28] Although transporting water to the home from an offpremises source has been associated with contamination in other studies, 15,17 in this population, microbiologic quality of stored water tended to be similar to, or better than, source water. Under conditions of relatively high-quality source water as in this study, microbial settling and time-related die-off are unlikely to yield significant improvement in water quality.…”
Section: Discussionmentioning
confidence: 98%
“…These results are consistent with the findings of other studies that demonstrated improved sources are not necessarily safe. 5,6,8,[25][26][27][28] Although transporting water to the home from an offpremises source has been associated with contamination in other studies, 15,17 in this population, microbiologic quality of stored water tended to be similar to, or better than, source water. Under conditions of relatively high-quality source water as in this study, microbial settling and time-related die-off are unlikely to yield significant improvement in water quality.…”
Section: Discussionmentioning
confidence: 98%
“…Access to safe water is a serious public health concern in Haiti, the nation with the poorest water and sanitation infrastructure in the Western Hemisphere [1]. The World Health Organization (WHO) estimates only 62% of Haitians have access to “improved water” sources [2].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into consideration the fact that improved drinking water is not necessarily safe water [6, 7] the proportion of the country’s rural population at an elevated risk of poor health due to exposure to contaminated drinking water is probably much higher than estimates indicate. In fact, the majority of those living in the countryside must rely on drinking untreated or unimproved water at least part of the time [1, 7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of access to water and sanitation services has identified the continuing and large unmet needs, and helped to inform efforts to improve these services 16. Sustained efforts will be necessary to achieve long-term improvements 9…”
mentioning
confidence: 99%